2021
DOI: 10.3389/fpubh.2021.683683
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Air Pollution and Acute Coronary Syndromes During Lockdown for COVID-19: Results From the Terni Hub Center

Abstract: Background: During the lockdown for COVID-19, a massive decrease in hospital admissions for acute coronary syndrome (ACS) and a drop in air pollution were both detected in Italy. Our aim was to investigate the possible association between these two events at the Province of Terni, one of the most polluted urban and industrial area in Central Italy.Methods: We analyzed data of daily 24-h urban air concentrations of particulate matter (PM)10 and PM2.5 from fixed station monitoring network located in the main cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Since the symptom-onset-to-first-medical-contact time plays a crucial role in a longer delay, and patients presented with higher levels of emotional and symptomatic fear expressions than the general population, a major cause of this delayed presentation could be attributable to changes in patient behavior and risk perception, which arouses reluctance to come to the hospital for fear of contracting COVID-19, as confirmed by the patients themselves in previously published reports [ 42 , 43 ]. Interestingly, recent data have not confirmed the association between a decrease in hospital admissions for acute coronary syndrome and a decrease in air pollution due to lockdown containment measures, indirectly giving strength to other hypotheses for the drop observed in AMI procedures [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the symptom-onset-to-first-medical-contact time plays a crucial role in a longer delay, and patients presented with higher levels of emotional and symptomatic fear expressions than the general population, a major cause of this delayed presentation could be attributable to changes in patient behavior and risk perception, which arouses reluctance to come to the hospital for fear of contracting COVID-19, as confirmed by the patients themselves in previously published reports [ 42 , 43 ]. Interestingly, recent data have not confirmed the association between a decrease in hospital admissions for acute coronary syndrome and a decrease in air pollution due to lockdown containment measures, indirectly giving strength to other hypotheses for the drop observed in AMI procedures [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the concentration of most air pollutants decreased transiently during the lockdown in France, to a greater or lesser extent depending on the geographical area and its baseline pollution level [ 21 ]. But interestingly, a study specifically investigating the relation between the hospital management of ACS during the lockdown and air pollutants found no association between an short term air cleaning effect and a concomitant reduction in invasive procedures for ACS [ 22 ]. These facts raise questions about the impact of a transient and geographically heterogeneous decrease in air pollutants on the occurrence of ACS, and how it may have interacted with the other factors considered.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the incidence of ACS, periprocedural mortality resulting from this disease, and the incidence of COVID-19 has not been sufficiently reported in the literature [ 41 ]. In a relatively small Italian study evaluating the number of hemodynamic procedures in ACS in the province of Terrini in 2020—the first year of the pandemic—they found that the number of hemodynamic procedures decreased.…”
Section: Discussionmentioning
confidence: 99%